Differences of Blended Learning Assisted by Videoscribe Learning Media and Conventional Learning on Mathematics Learning Outcomes of Class X Students of SMA Negeri 1 Kualuh Leidong - Afny Arti Sinaga; Bornok Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the differences between videoscribe-assisted blended learning and conventional learning in improving the mathematics learning outcomes of class X students of SMA Negeri 1 Kualuh Leidong. Based on the results of data analysis, it can be concluded that there are differences in blended learning assisted by videoscribe learning media and conventional learning in improving the mathematics learning outcomes of class X students of SMA Negeri 1 Kualuh Leidong with the following results, namely the initial ability test of students before treatment (pretest) in the control class has a value the average is 28.5 and in the experimental class is 21.00 for it can be seen that the ability of students' early mathematics learning outcomes is at very low criteria while for the final student ability test after treatment (posttest), namely by applying blended learning assisted learning media videoscribe.